Faktor-Faktor Yang Mempengaruhi Konsumen Menggunakan Jasa Pengiriman PT Pos Indonesia (Soreang) - Irma Widya (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
The research aimed to determine the effect of price, location, and service quality on the decision of use services of PT. Pos Indonesia, Soreang, Kabupaten Bandung. The population in this study was consumers who had used the services of PT Pos Indonesia, Soreang. The sampling collection technique used accident sampling with a total of 100 respondents. The data analysis technique used in this research is multiple linear regression. The result of multiple linear regression analysis shows that the variables of price, location and service quality simultaneously have a positive relation to consumer decision. Based on the results of the f test, it shows that the variables of price, location, and service quality simultaneously have a positive and significant impact on consumers decisions. The result of the coefficient of determination is 0.55 or 55%, meaning that independent variables such as price, location, and service quality can explain variations in consumer decisions to choose the delivery service of PT Pos Indonesia (Soreang). While the remaining 45% of other variables not examined in this study. Company management should pay attention to parking spaces and price competitiveness to increase consumer interest in using the delivery service of PT Pos Indonesia (Soreang).